2013
DOI: 10.3109/14767058.2013.831067
|View full text |Cite
|
Sign up to set email alerts
|

Routine cervical length and fetal fibronectin screening in asymptomatic twin pregnancies: is there clinical benefit?

Abstract: In twin pregnancies, routine CL and fFN screening does not reduce the risk of PTB or SPTB. However, the routine use of these tests is associated with significantly improved ACS exposure and timing for women who deliver preterm without increasing ACS exposure to women who deliver at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…147 Although the rates of preterm birth were similar between the two groups, the routine use of these tests was associated with significantly improved rates and timing of antenatal corticosteroid administration among patients who delivered prematurely. These findings suggest that routine measurement of sonographic CL and fetal fibronectin could potentially improve the perinatal outcomes in twin gestations delivered preterm by increasing antenatal corticosteroid exposure.…”
Section: Discussionmentioning
confidence: 86%
“…147 Although the rates of preterm birth were similar between the two groups, the routine use of these tests was associated with significantly improved rates and timing of antenatal corticosteroid administration among patients who delivered prematurely. These findings suggest that routine measurement of sonographic CL and fetal fibronectin could potentially improve the perinatal outcomes in twin gestations delivered preterm by increasing antenatal corticosteroid exposure.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, we have shown previously from retrospective data that these screening tests could potentially improve antenatal corticosteroid administration rates to twins delivered prior to 34 weeks. 27 Ultimately, however, until a prospective study that randomizes twin pregnancies to routine screening or no screening demonstrates significant benefit with routine screening, the decision whether or not to use these tests routinely needs to be individualized.…”
Section: Discussionmentioning
confidence: 99%
“…Better detection of women at risk of PTB is important for patient counseling and can guide decisions regarding patient transfer, admission, frequency of monitoring, and administration of corticosteroids for fetal lung maturation. Indeed, in a recent study, serial monitoring of CL in twins was associated with improved rates of exposure to corticosteroids in women who delivered preterm, 46 although data regarding the beneficial effects of antenatal corticosteroids in twins pregnancies are conflicting. 113123 In addition, in a recent individual-patient meta-analysis, Romero et al found that the use of progesterone in asymptomatic women with twin pregnancy and a short cervix decreased the rate of PTB at <33 weeks by 30% and the rate of neonatal morbidity by approximately 50%.…”
Section: Commentsmentioning
confidence: 99%